1998
DOI: 10.1007/bf02258359
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of tyrosine kinases in normal and cancer cells

Abstract: As the post-genome era is approaching, with vast amount of sequence information available and new technology developed, scientists are presented with opportunities to explore in simple analysis the structure and expression pattern of not just a single gene, but of an entire family of genes, if not the entire genome. The concept of 'molecular profiling' or 'expression array' has thus emerged. The need to simultaneously 'see' all genes in the same family is obvious under the precept of the combinatorial process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Because of the importance of tyrosine kinases in cellular control, we focused our investigation on the identification of Zta-regulated tyrosine kinases. Taking advantage of a two-step kinase display system, the tyrosine kinase profiles of Zta-expressing and control cells were displayed following amplification of tyrosine kinase transcripts using degenerate primers, which were based on the conserved DVW and DFG motifs found in most tyrosine kinases (27). The advantage of this newly developed assay is that each tyrosine kinase may be recognized by its unique restriction enzyme digestion pattern in the variable regions between the DVW and DFG motifs (27).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Because of the importance of tyrosine kinases in cellular control, we focused our investigation on the identification of Zta-regulated tyrosine kinases. Taking advantage of a two-step kinase display system, the tyrosine kinase profiles of Zta-expressing and control cells were displayed following amplification of tyrosine kinase transcripts using degenerate primers, which were based on the conserved DVW and DFG motifs found in most tyrosine kinases (27). The advantage of this newly developed assay is that each tyrosine kinase may be recognized by its unique restriction enzyme digestion pattern in the variable regions between the DVW and DFG motifs (27).…”
Section: Resultsmentioning
confidence: 99%
“…Taking advantage of a two-step kinase display system, the tyrosine kinase profiles of Zta-expressing and control cells were displayed following amplification of tyrosine kinase transcripts using degenerate primers, which were based on the conserved DVW and DFG motifs found in most tyrosine kinases (27). The advantage of this newly developed assay is that each tyrosine kinase may be recognized by its unique restriction enzyme digestion pattern in the variable regions between the DVW and DFG motifs (27). Analysis of the restriction profiles revealed that the most prominent, differentially regulated tyrosine kinase in the Zta-expressing clones is TKT (also known as DDR2) (23).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations